TEACHING READING COMPREHENSION THROUGH READER RESPONSE APPROACH TO THE FOURTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT PGRI UNIVERSITY - Yusri - (Politeknik Negeri Sriwijaya, 2011)
The objective of conducting this study was to see whether or not there was any significant difference in reading comprehension achievement of the students before and after being taught by using Reader Response Approach. For this purpose, the experimental research was used. The samples of this study were the fourth semester students of English Education Study Program, Faculty of Teacher Training and Education PGRI University in the academic year of 2007/2008. The primary data were obtained by means of test. The result shows that there was a statistically significant difference in reading comprehension achievement of the students’ pre-test and post-test after being taught by using Reader Response Approach. It was found that the t-obtained (7,25) was higher than t-table (2,145). It was also found that mean scores of the students’ post-test was (7,71) while the mean score of the students’ pre-test was (6,26). In other words, teaching reading by using Reader Response Approach was effective.